1985
DOI: 10.2466/pms.1985.60.1.11
|View full text |Cite
|
Sign up to set email alerts
|

ARE the Accessory Facial Movements of the Stutterer Learned Behaviours?

Abstract: The purpose of the present study was to explore the accessory nonverbal behaviours emitted by stutterers when their speech was fluent, normally disfluent, or stuttered. Subjects were 25 stutterers who were required to speak spontaneously for a 2-min. period. Seven types of nonverbal behavior were observed. Significant differences among the three speech categories were obtained for jaw movements, mouth movements, forehead movements, eyebrow movements, and head movements. Eyelid movements and eye blinks were non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, Kraaimaat and Janssen (1985) have pointed out that support for this contention is somewhat limited since it rests predominantly on studies which have shown that secondaries can be brought under stimulus control (Brutten & Shoemaker, 1967;Martin & Siegel, 1966a, 1966b. In addition, Kraaimaat and Janssen (1985) pointed to both Lanyon's (1978) suggestion that at least certain nonverbal accessory behaviors might be a result of speechassociated physical struggle and their own contention that some secondaries could be a physical result of classically conditioned speech anxiety (Janssen & Kraaimaat, 1986). In any event, Kraaimaat and Janssen's (1985) investigation of the oro-facial structure of the segments of their participants' speech that was fluent, normally disfluent or stuttered led them to conclude that "the actual function of the nonverbal behaviours emitted by stutterers is not fully clear" (p. 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kraaimaat and Janssen (1985) have pointed out that support for this contention is somewhat limited since it rests predominantly on studies which have shown that secondaries can be brought under stimulus control (Brutten & Shoemaker, 1967;Martin & Siegel, 1966a, 1966b. In addition, Kraaimaat and Janssen (1985) pointed to both Lanyon's (1978) suggestion that at least certain nonverbal accessory behaviors might be a result of speechassociated physical struggle and their own contention that some secondaries could be a physical result of classically conditioned speech anxiety (Janssen & Kraaimaat, 1986). In any event, Kraaimaat and Janssen's (1985) investigation of the oro-facial structure of the segments of their participants' speech that was fluent, normally disfluent or stuttered led them to conclude that "the actual function of the nonverbal behaviours emitted by stutterers is not fully clear" (p. 16).…”
mentioning
confidence: 99%
“…Specifically, it was the purpose of this investigation to provide between-and within-group analyses of the particular secondary adjustments that they reportedly employ as a means of coping with the anticipation and/or presence of speech disruption. The focus of this study was on these speech-associated coping responses because they are commonly held to be the most typical forms of secondaries (Kraaimaat & Janssen, 1985).…”
mentioning
confidence: 99%